Вирішення лінійних систем за допомогою декомпозиції - Zaitsev, D. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Special subsets of equations of linear system named by clans were introduced and studied. It was proposed to use the decomposition into clans for the acceleration of linear system solving. Decomposition complexity equals cube depending on size of system. Therefore, acceleration of computations was obtained for methods with complexity exceeding cube. For integer systems solving in nonnegative integer numbers acceleration of computations obtained is exponential.